Efektivitas Antibakteri Ekstrak Daun Glodokan Tiang (Polyalthia longifolia) Terhadap Cutibacterium acnes dan Staphylococcus epidermidis - Girsang, Valentina; Nufus , Nunky; Saptawati , Tunik; Sa’adah , Anifatus; Wibowo, Anisa Devi Kharisma; Vidiani , Anak Agung Pradnya Paramitha (Journal of Pharmaceutical and Sciences, 2025)
Introduction: Polyalthia longifolia, commonly known as Glodokan tiang, is a plant typically found along roadsides, serving as shade and an ornamental feature in gardens. In addition to its aesthetic function, the leaves of this plant have been found to contain compounds with effective antibacterial activity. Natural ingredients with antibacterial properties, such as Polyalthia longifolia leaf extract, can be an alternative acne treatment due to their lower side effects than chemical drugs. Research Objective: This study aims to test the antibacterial activity of Polyalthia longifolia leaf extract in inhibiting the growth of Staphylococcus epidermidis and Cutibacterium acnes, which are significant causes of acne. Research Method: Polyalthia longifolia leaves were extracted using a maceration method with 70% ethanol as the solvent. The resulting extract was then tested for antibacterial activity using the disc diffusion method at 30%, 35%, 40%, 45%, and 50%. The bacteria used in the tests were Staphylococcus epidermidis and Cutibacterium acnes. Clindamycin was used as a positive control, and sterile water was used as a negative control. The data obtained from the tests were analyzed using the Kruskal-Wallis and post-hoc Games-Howell tests. Results: The study showed that Polyalthia longifolia leaf extract at various concentrations (30%, 35%, 40%, 45%, 50%) exhibited significant antibacterial activity against both bacteria tested. At a concentration of 50%, the extract demonstrated the most potent inhibitory effect on Cutibacterium acnes and Staphylococcus epidermidis, with inhibition zones reaching 15.82 mm and 15.74 mm, respectively. Conclusion: Polyalthia longifolia leaf extract shows significant antibacterial potential against Staphylococcus epidermidis and Cutibacterium acnes. The 50% extract concentration exhibited the most potent inhibitory effect, making it a promising candidate for natural acne treatment with minimal side effects.